The Influence Of The Work Environment And Organizational Culture On Employee Performance With Satisfaction As An Intervening Variable - Ekasari Dimbarokke; Siti Haerani; Muhammad Ismail (STIE AMKOP, 2023)
This study aims to analyze the influence of the work environment and organizational culture on employee performance with satisfaction as an intervening variable in PT. Bank BNI Makassar branch. The population in this study is employees at PT Bank BNI Makassar Branch, including all employees ranging from outsourcing employees, BINA's employees, and permanent employees totaling 238 employees. Sampling in this study used purposive sampling method. Data collection techniques used by distributing questionnaires. The data analysis technique used is path analysis. The results of this study show that (1) The work environment has a positive and significant effect on job satisfaction. The refore hypothesis one is accepted. (2) Organizational culture has a positive and significant effect on job satisfaction, so hypothesis two is accepted. (3) The work environment has a positive and significant effect on employee performance. The refore hypothesis three is accepted. (4) Organizational culture has a positive and significant effect on employee performance, so hypothesis four is accepted. (5) Job satisfaction has a positive and significant effect on employee performance, so hypothesis five is accepted. (6) Work environment through job satisfaction as an intervening variable has a positive and significant effect on employee performance. The refore hypothesis six is accepted. (7) Organizational culture through job satisfaction as an intervening variable has a positive and significant effect on employee performance, so hypothesis seven is accepted. Keywords: Work Environment, Organizational Culture, Employee Performance and Satisfaction.